PENGARUH PARTISIPASI PENYUSUNAN ANGGARAN DAN KEJELASAN SASARAN ANGGARAN TERHADAP KINERJA APARAT PEMERINTAH DAERAH KABUPATEN SIAK DENGAN KOMITMEN ORGANISASI SEBAGAI VARIABEL MODERATING (Studi Empiris pada Satuan Kerja Perangkat Daerah Kabupaten Siak) - Zein, Muhammad; Basri, Yessy Mutia; ', Supriono (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
The aim of this study was to test the effect of budget participation and budget goal clarity on the performance of government officials, organizational commitment as moderating variables. The population in this study was the entire leadership of SKPD Siak, head of the financial and Planning section. The sampling technique used was purposive sampling, with a total sample of 93 respondents. This research was conducted using questionnaires and multiple linear regression analysis was used to analyze the data with SPSS version 20.0. The statistical results showed that budget participation and budget goal clarity affects on performance of government officials with the adjust R square of 41,5%. Organizational commitment variable affecting the relationship between budgetary participation and budget goal clarity on the performance of government officials with the adjust R square of 47,3%.Keywords : participation, budget, performance, government and, commitment.